ANALISIS POTENSI EKONOMI KECAMATAN PINOGU KABUPATEN BONE BOLANGO - Machmud, Joice; Mokodompit, Nur Eng; Sahi, Liviandi (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2023)
The economic potential of an area becomes the basic capital in development, therefore for the benefit of development planning, it is necessary to analyze the potential and carrying capacity of an area. This study aims to identify the economic potential of Pinogu District as an isolated and difficult to reach area. This research uses a quantitative approach, and the data sources that are the basis of the analysis are secondary data that are already available both in sub-districts in numbers, as well as data available in sub-districts. Alat analisis yang digunakan adalah Locatioan Question (LQ). The results of the study concluded that the results of the research analysis showed that the economic potential of the Pinogu District area showed that it was not optimal to encourage the growth and development of the Pinogu District area in the 2017-2021 period. The results of the analysis using the Location Question (LQ) showed that the average in the 2017-2021 period of LQ values was less than one (0.95). This value means that the commodity of agricultural products consisting of the food crop sub-sector, fisheries sub-sector, plantation sub-sector, and forestry sub-sector is not yet a base commodity, and is only categorized as a non-base sector.